Pristimerin as a Novel Hepatoprotective Agent Against Experimental Autoimmune Hepatitis - El-Agamy, Dina S.; Shaaban, Ahmed A.; Almaramhy, Hamdi H.; Elkablawy, Sarah; Elkablawy, Mohamed A. (Frontiers in Pharmacology, 2018)
Pristimerin (Pris) is bioactive natural quinonoid triterpene that has anti-inflammatory and anti-cancer activities. Meanwhile, its effect against hepatitis needs to be elucidated. This investigation aimed to evaluate the ability of Pris to protect against autoimmune hepatitis (AIH). A mouse model of AIH was established using single concanavalin A (Con A) intravenous injection. Mice were treated with Pris at two different doses (0.4 & 0.8 mg/kg) for 5 days prior to Con A challenge. Markers of hepatic injury, oxidative, inflammatory and apoptotic damage were estimated. Results have revealed that Pris pretreatment ameliorated Con A-induced hepatic damage. There was decrease in the elevated serum indices of hepatic damage (ALT, AST, ALP and LDH) and improvement of the histopathological picture of the liver. Pris effectively decreased Con A-induced neutrophil infiltration into the hepatic tissue as presented by amelioration of the level and immuno-expression of myeloperoxidase (MPO). Additionally, Pris attenuated Con A-induced increase in CD4+ T-cells in hepatic tissue. Lipid peroxidation was significantly depressed simultaneously with enhancement of the antioxidant capacity in Pris pretreated animals. Pris also enhanced nuclear factor erythroid 2-related factor 2 (Nrf2) mRNA expression and its binding capacity. In addition, Pris increased mRNA expression of heme-oxygenase-1 (HO-1) and restored its normal level. Furthermore, Pris decreased the level and immuno-expression of nuclear factor kappa-B (NF-κB) as well as the downstream inflammatory cascade (TNF-α, IL-6 and IL-1β). Finally, Pris showed inhibitory effect on Con A-induced apoptotic alteration in liver as it decreased the mRNA expression and levels the apoptotic markers (Bax and caspase-3) and increased mRNA expression and level of the anti-apoptotic protein (Bcl2). In conclusion, this study demonstrates the potent hepatoprotective efficacy of Pris against Con A-induced hepatitis which may be related to anti-oxidative, anti-inflammatory and anti-apoptotic pathways. Pris could serve as a new candidate for the management of hepatitis.